Deconstructing The Concept of “Green Deen” By Abdul Martin and Its Implementation for Boarding Schools in The City of Kediri - Solichin, Moh. Badrus; Bahtiar, Moh. David (Proceeding International Conference on Education, 2023)
The root of problem of this research begins with nature of humans who are positioned as caliphs on earth, and are mandated to maintain sustainability and not act antropocentrically towards nature and its ecosystem. Then researchers discovered the fact that from students in Islamic boarding schools movement could be created to protect and preserve natural ecosystems, as well as behaving in a friendly manner towards the environment according to the teachings of the Islamic religion. Through this research the author will examine this issue by deconstructing Abdul Matin's "Green Deen" concept. This research is a literature study, which examines 6 Green Deen concepts that will be implemented in the lives of students in Islamic boarding schools in Kediri City. The results of this research include analyzing Abdul Matin's Green Deen theory into 6 concepts that can be implemented into daily lives of students in Islamic boarding schools in Kediri City.